Aplikasi Sistem Satuan Kegiatan Mahasiswa pada FILKOM Apps Fakultas Ilmu Komputer Menggunakan Aplikasi Berbasis Web - Reynaldi Ricky Putra Utama Guinta; Denny Sagita Rusdianto; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Student Activity Unit is one of the facilities provided by the Faculty of Computer Science, Brawijaya University for students to facilitate and store information related to various kinds of student activities internally and externally. From the start of the competition, official activities, organization and participation in both levels of Study Program, Faculty, Regional, National and International. System applications that already exist and are already running in one of the Filkom Applications Applications with a feature called SKM, which is in accordance with business processes and implementation in the field has not yet run with that caused by a shortage of Human Resources (HR) in Student Affairs, so the process in verification itself is still hampered. The Student Activity Unit also helps students in helping and storing information related to student activities. The information stored on the application itself also helps in the process of accreditation of the Faculty of Computer Science, Brawijaya University. But in the application in the field there are still problems because there is still a lot of information that has not been stored correctly. To overcome this problem, a Web Application using the Codeiginter framework is created specifically for the Student Activity Unit which is needed to help overcome student problems related to lack of human resources, involving students (Student Executive Board) as a verification unit and also providing tools to store information related to students as one of the needs needed for accreditation.